1999
DOI: 10.1007/s004170050339
|View full text |Cite
|
Sign up to set email alerts
|

Grid laser treatment in macular branch retinal vein occlusion

Abstract: We hypothesize that the abrupt ischemic damage subsequent to MBRVO is the main factor causing the central function impairment. Grid laser treatment is not able to reduce the macular edema more than the natural evolution, and does not improve visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 5 publications
2
41
0
Order By: Relevance
“…[2][3][4][5] It has also been suggested that even in I-BRVO patients with intact foveal avascular zones, improvement with treatment may not be significantly different from that seen in the natural history of I-BRVO patients as a group. [6][7][8] Clearly, the patients in this study benefited from treatment, most remarkably Cases 1 and 3 where ischaemia extended into the foveal avascular zone. When comparing these results with previous studies, it is noteworthy that in each case, the grid laser treatment applied was more intense than Branch Vein Occlusion Study Group 2 recommendations.…”
Section: Commentmentioning
confidence: 71%
“…[2][3][4][5] It has also been suggested that even in I-BRVO patients with intact foveal avascular zones, improvement with treatment may not be significantly different from that seen in the natural history of I-BRVO patients as a group. [6][7][8] Clearly, the patients in this study benefited from treatment, most remarkably Cases 1 and 3 where ischaemia extended into the foveal avascular zone. When comparing these results with previous studies, it is noteworthy that in each case, the grid laser treatment applied was more intense than Branch Vein Occlusion Study Group 2 recommendations.…”
Section: Commentmentioning
confidence: 71%
“…All of the patients had significant macular edema, which was defined as retinal thickening at least one optic disc area in size that involved the fovea [11]. The following exclusion criteria were employed for this study: (1) previous ocular surgery or vitreous injection of anti-VEGF agents and triamcinolone acetonide, (2) previous retinal photocoagulation (including macular photocoagulation), (3) diabetes mellitus with diabetic retinopathy, (4) iris rubeosis, and (5) a history of ocular inflammation and vitreoretinal disease.…”
Section: Methodsmentioning
confidence: 99%
“…Significant macular oedema was defined as retinal thickening of one optic disc area or greater in size, involving the fovea. 17 The exclusion criteria for this study were as follows: (1) previous ocular surgery, (2) patients with diabetes mellitus and diabetic retinopathy, (3) patients with iris rubeosis, (4) a history of ocular inflammation and vitreoretinal disease, and (5) patients who had the complications, such as intraoperative capsule breaks and dialysis during cataract surgery and long duration (over 20 min) of cataract surgery to avoid the possibility of influence of the vitreous levels of VEGF and IL-6. Combined vitrectomy and cataract operation was performed at the Hiroshima University School of Medicine and Hiroshima Prefectural Hospital.…”
Section: Methodsmentioning
confidence: 99%